Relationship of Work in Pandemic Era with Increased Risk of Musculosceletal Disorders that Lead to Change in Cervical Posture - Dea Linia Romadhoni; Alinda Nur Ramadhani; Exda Hanung Lidiana (Masters Program in Public Health, 2021)
Background: Musculoskeletal Disorders (MSDs) was a form of complaints that occur in muscles, bones, joints, ligaments and tendons. Globally, musculoskeletal disorders were the single largest cause of work-related health complaints with more than 33% of all new diseases reported. Risk factors that contribute to caused MSDs were social factors. This study aimed to analyze the relationship between social factors related to the risk of MSDs and their effect on changes in cervical posture.Subjects dan Method: This was a cross-sectional study. A sample of 32 were selected for this study with. The sampling technique used was total sampling according to the inclusion and exclusion criteria. This study was conducted online through the google-form application by respondents in Surakarta, Central Java from March 2021 to May 2021. The dependent variable was changes in cervical posture. The independent variable was the respondent's characteristics such as work environment and work posture. The data analysis technique used Chi Square test.Results: The results of the analysis using the Chi Square test showed that there was a relationship between work duration and work risk factors with OR= 9.00; 95%CI= 1.72 to 46.9; p=0.010. Based on these results, it can be interpreted that workers with working duration >7 hours per day are 9 times more likely to have a high risk injury risk factor compared to workers who work <7 hours a day. The results of the analysis with the Chi Square test showed that there was a relationship between risk factors for injury and a high risk work environment with forward head posture with OR= 20.00; 95%CI= 2.11 to 189; p=0.003). Workers with risk factors for injury and a high risk work environment are 20 times more likely to experience forward head posture compared to workers with risk factors for injury and a risky work environment.Conclusion: There is a relationship between duration of work with work risk factors, there is a relationship between environmental factors and risk factors for injury and there is a relationship between risk factors for injury and a high-risk work environment with forward head posture.Keywords: pandemic era, musculosceletal disorders, cervical posture change.Correspondence: